Determinants for the use of A GPN Debit Card (National Payment Gateway) by Students FEBI UIN SYAHADA Padangsidimpuan - Hamid, Azwar; Arfah, Lita; Rambe, Lulu Walmarjan (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2022)
The discussion in this study relates to service features, security systems, and student's knowledge of the use of debit cards with GPN. In this regard, the approach taken is theories related to the field. The type of research used is field research (field research) which is quantitative in nature. The samples used in this study were 74 respondents. The sampling technique used was a purposive sample, and the data collection techniques used were interviews, documentation, and questionnaires. Data analysis used was a validity test, reliability test, descriptive statistical analysis, normality test, multicollinearity test, heteroscedasticity test, coefficient of determination test (R2), multiple linear regression analysis test, t test (Partial), F test (Simultaneous) using SPSS tools 23. The results of this study this show that service features, security, and knowledge are factors that influence the use of GPN debit cards by students at the Faculty of Islamic Economics and Business UIN SYAHADA Padangsidimpuan.